Indonesian Islamic Studies: A Select Dissertation Bibliography 1980-1999 - Saputro, M. Endy (DINIKA : Academic Journal of Islamic Studies, 2016)
Continuing the previous edition, this bibliography presents dissertations titles produced mainly from universities in Australia, America, and Canada. Not only dissertations ones, some important theses are also displayed in this bibliography. The period 1980-1999 is a salient period in the process of Indonesian Islamic studies development. Since 1990 Minister of Religious Affairs has selectively sent Indonesian scholars finishing their master degree to McGill University. For the result, they produced theses master on Indonesian Islam. On the one hand, this theses can be used as an evidence that Indonesian scholars were able to âintroduceâ Indonesian Islam abroad; on the other hand, this introduction focuses on leaders thoughtâwhich is then dominated the pattern of Islamic studies in Indonesian Islamic higher education institutions. In comparison, dissertation/thesis from the universities in the United States and Australia shows notable interesting assumption that during that period the scholars whose background are Islamic studies tend to produce theological-doctrinal dissertation/thesis as well as that of leaders-thought; while scholars with social and cultural background tend to review Islam from the attending problems in society.Keywords: Islamic Studies, McGill University, Bibliography, Dissertation, IndonesiaÂ Â